Preparation method of fluorescent MOF
By using high borosilicate aluminum cover glass bottles to prepare fluorescent MOFs under normal pressure, the problems of high equipment costs, high safety risks and difficult to observe the crystal formation process in the prior art are solved, and the effects of cost reduction, safety improvement and visual control of experimental processes are achieved.
Patent Information
- Application Number
- CN202411761041.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-04
AI Technical Summary
The existing MOF preparation methods have problems such as high equipment costs, high experimental safety risks and difficulty in observing the crystal formation process.
A lower-cost high borosilicate aluminum-cap glass bottle is used to prepare fluorescent MOFs by stirring, heating and cooling steps under normal pressure to achieve visual control of the reaction process.
The cost of experimental equipment is reduced, the experimental safety is improved, and the control effect of the experimental process is improved through visual monitoring.
Smart Images

Figure CN119751898A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coordination polymers, and in particular to a method for preparing a fluorescent MOF. Background Art
[0002] Traditional inorganic and organic luminescent materials have been widely explored by scientists due to their diverse functions and applications in lighting, display, sensing and optical devices. Some inorganic luminescent materials, such as BaMgAl 10 O 17 :Eu 2+ and GdMgB5O 10 :Ce 3+ , Tb 3+ , have been commercialized and used in blue and green lamps. The main advantage of these two materials is the high purity of the luminescent color. However, there are also many disadvantages, such as the inhomogeneity of the components, the particle size, the microstructure and the interface, which may affect the luminescent properties of inorganic luminescent materials.
[0003] Metal-organic frameworks (MOFs), a new type of organic-inorganic hybrid material, are very promising as multifunctional luminescent materials because both the inorganic and organic parts can provide luminescent platforms, and the charge transfer between metal-ligands within MOFs can also increase the luminescent function. In addition, some guest molecules within MOFs can also emit and / or induce luminescence. The exploration of functional luminescent MOFs is increasing. The characteristic of luminescent MOFs, which is different from traditional inorganic and organic luminescent materials, is that the stable porosity enables it to reversibly store and release guest molecules, providing a host for identifying differences in sensing substances. Some fluorescent MOFs can be used to detect explosives DNT and DMNB (2,3-dimethyl-2,3-dinitrobutane), and have the characteristics of fast response speed and high sensitivity. Within 10 seconds, the fluorescence quenching percentages of MOFs films for DNT and DMNB are about 85% and 84%, respectively.
[0004] However, the preparation of MOF currently has the following problems: (1) The commonly used preparation method is hydrothermal synthesis, and the hydrothermal synthesis reactor is generally composed of a polytetrafluoroethylene lining and a stainless steel shell, and the equipment cost is relatively high; (2) The hydrothermal synthesis method mainly uses high temperature and high pressure reaction conditions. The reactor that is under high temperature and high pressure reaction conditions for a long time in the laboratory has great hidden dangers; (3) The hydrothermal reactor composed of a polytetrafluoroethylene lining and a stainless steel shell is made of opaque material, which makes it difficult to observe the entire crystal formation process, which is not conducive to experimental process control. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of this application is to provide a method for preparing fluorescent MOFs, using lower-cost equipment and preparing a new type of fluorescent MOF under normal pressure. During the preparation of MOFs, the reaction situation can be observed through a transparent glass bottle, and the reaction process can be visually controlled.
[0006] To achieve the above problem, the present application discloses a method for preparing a fluorescent MOF, characterized in that: the fluorescent MOF has {[Zn (tdc) (DMF)]·1.5 DMF} n The fluorescent MOF is prepared by the following steps: (1) The organic ligands thiophene-2,5-dicarboxylic acid (H2tdc), Zn 2+ The salt is weighed in a molar ratio of (0.15-0.25): (0.15-0.25), added into N,N-dimethylformamide (DMF) solvent, and stirred with a magnetic stirrer in air to obtain a colorless transparent clear liquid; (2) Transfer the obtained colorless transparent clear liquid into a glass bottle with an aluminum cap, heat it in an oven to 90-120°C and maintain it for 40-72 hours, and then cool it to room temperature at a rate of 10°C per hour; (3) Washing with DMF yields a large amount of colorless, transparent block crystals; the prepared crystals are fluorescent MOFs.
[0007] Furthermore, the Zn 2+ The salt is selected from at least one of Zn (NO3)2•6H2O, zinc acetate and zinc sulfate, wherein Zn (NO3)2•6H2O is more preferred. .
[0008] Furthermore, H2tdc and Zn 2+ The molar weights of the salts are (0.15-0.25) mmol and (0.15-0.25) mmol respectively, and the amount of DMF used as the solvent is 8-12 ml, with 10 ml being more preferred.
[0009] Furthermore, the stirring time in step (1) is 5-15 min. The heating temperature in step (2) is 100° C. and the heating time is 48 h.
[0010] Furthermore, the basic crystallographic data of the fluorescent MOF are: T = 293 K; Crystal system: Hexagonal; space group: R-3; a = 20.2178 (3) Å; b = 20.2178 (3) Å; C = 41.8385 (7)Å; α = 90°, β = 90°, γ = 120°, V = 14810.6 (4) Å3; Z = 36; ρcalcd = 1.513 Mg m-3; μ = 3.84 mm-1; θmax = 76.8°; 3424independent reflections (Rint = 0.019); R1 = 0.112; wR2 = 0.470; GOF = 2.30.
[0011] Furthermore, the fluorescent MOF belongs to the Hexagonal crystal system R-3 space group; the SBU of the fluorescent MOF is two Zn 2+ The ions, Zn1 and Zn2, are both five-coordinated trigonal bipyramidal geometric structures, while the tdc ligand adopts a coordination mode: (η1-η1)-(η1-η2-μ2)-μ4 (tdc); the two Zn (II) ions are bridged by two DMF dimers and the carboxyl groups of four different tdc ligands to form a binuclear [Zn2(COO)4(O)2]; these binuclear units are connected by four tdc ligands in the ab plane to form a two-dimensional layer with a 4-connected kgm (kagome) network; the fluorescent MOF uses the center point of the binuclear unit as a node, and the ligands are simplified to lines, forming a layer of a 4-connected kgm network; the three-dimensional stacking diagram of the fluorescent MOF is the stacking of two-dimensional layers in the c-axis direction to form a one-dimensional channel; from a topological point of view, the framework of the fluorescent MOF can be described as a kgm network with Schlafli symbols.
[0012] Furthermore, the fluorescent MOF was washed with DMF, filtered, and dried at room temperature before powder diffraction testing. The main diffraction peaks (2θ) were located at 6.809°, 9.72°, 12.96°, and 15.50°, corresponding to the (100), (110), (-1-11), and (-111) crystal planes, respectively.
[0013] Furthermore, the emission spectrum of the fluorescent MOF tested at an excitation wavelength of λex = 396 nm is 469 nm, and the CIE chromaticity diagram shows that it emits blue light; Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses a borosilicate glass bottle with an aluminum cap, which has a lower manufacturing cost, reducing the cost of experimental equipment by more than 100 times; (2) The present invention adopts a normal pressure method to prepare fluorescent MOF, which reduces the potential safety hazards of long-term use of high-temperature and high-pressure equipment in experiments, and the entire experimental process is safer; (3) The borosilicate glass bottle reaction equipment used in the present invention is colorless and transparent, and the entire experimental process can be visually monitored. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0015] Figure 1 Schematic diagram of the traditional MOF hydrothermal reaction preparation; Figure 2 This is a schematic diagram of the preparation of MOF in this patent; Figure 3 The structure diagram of the fluorescent MOF of the present invention, wherein a) the coordination environment diagram of the Zn2+ ion in compound 8, color code: Zn, light blue; O, red; C, green; S, yellow; N, blue; b) H2tdc coordination mode; c) two-dimensional layered structure diagram; d) kgm topology diagram; Figure 4 This is the XRD diagram of the fluorescent MOF of Example 2 of the present invention; Figure 5 This is the TG graph of the fluorescent MOF of Example 2 of the present invention; Figure 6 This is the fluorescence image of the fluorescent MOF of Example 2 of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0017] Example 1 A DMF (10 mL) solution containing H2tdc (H2tdc = thiophene-2,5-dicarboxylic acid; 25.8 mg, 0.15 mmol) and Zn (NO3)2·6H2O (0.15 mmol, 44.6 mg) was stirred in air with a magnetic stirrer for 5 min to obtain a colorless transparent clear solution, which was then transferred to a 10 mL glass bottle, heated to 90 °C and maintained for 40 hours, and then cooled to room temperature at a rate of 10 °C per hour. A large amount of colorless transparent block crystals {[Zn (tdc) (DMF)]·1.5DMF} were obtained by washing with DMF. n The relative purity of the bulk crystals was confirmed by XRD. The prepared bulk crystal samples were stored in DMF for subsequent characterization.
[0018] Example 2 A DMF (10 mL) solution containing H2tdc (H2tdc = thiophene-2,5-dicarboxylic acid; 34.4 mg, 0.2 mmol) and Zn (NO3)2·6H2O (0.2mmol, 59.5 mg) was stirred in air with a magnetic stirrer for 10 min to obtain a colorless, transparent clear solution, which was then transferred to a 10 mL glass bottle, heated to 100 °C and maintained for 48 hours, and then cooled to room temperature at a rate of 10 °C per hour. A large amount of colorless, transparent block crystals {[Zn (tdc) (DMF)]·1.5DMF} were obtained by washing with DMF. n The relative purity of the bulk crystals was confirmed by XRD. The prepared bulk crystal samples were stored in DMF for subsequent characterization.
[0019] Example 3 A DMF (12 mL) solution containing H2tdc (H2tdc = thiophene-2,5-dicarboxylic acid; 43 mg, 0.25 mmol) and Zn (NO3)2·6H2O (0.25 mmol, 74 mg) was stirred in air with a magnetic stirrer for 15 min to obtain a colorless, transparent clear solution, which was then transferred to a 15 mL glass bottle, heated to 100 °C and maintained for 72 hours, and then cooled to room temperature at a rate of 10 °C per hour. A large amount of colorless, transparent block crystals {[Zn (tdc) (DMF)]·1.5DMF} were obtained by washing with DMF. n The relative purity of the bulk crystals was confirmed by XRD. The prepared bulk crystal samples were stored in DMF for subsequent characterization.
[0020] Example 4 A DMF (10 mL) solution containing H2tdc (H2tdc = thiophene-2,5-dicarboxylic acid; 34.4 mg, 0.2 mmol) and zinc acetate (0.2 mmol, 36.6 mg) was stirred in air with a magnetic stirrer for 10 min to obtain a colorless transparent clear solution, which was then transferred to a 10 mL glass bottle, heated to 100 °C and maintained for 48 hours, and then cooled to room temperature at a rate of 10 °C per hour. A large amount of colorless transparent block crystals {[Zn (tdc) (DMF)]·1.5 DMF} were obtained by washing with DMF. n The relative purity of the bulk crystals was confirmed by XRD. The prepared bulk crystal samples were stored in DMF for subsequent characterization.
[0021] Example 5 A DMF (10 mL) solution containing H2tdc (H2tdc = thiophene-2,5-dicarboxylic acid; 34.4 mg, 0.2 mmol) and zinc sulfate (0.2 mmol, 32.2 mg) was stirred in air with a magnetic stirrer for 10 min to obtain a colorless transparent clear solution, which was then transferred to a 10 mL glass bottle, heated to 100 °C and maintained for 48 hours, and then cooled to room temperature at a rate of 10 °C per hour. A large amount of colorless transparent block crystals {[Zn (tdc) (DMF)]·1.5 DMF} were obtained by washing with DMF. n The relative purity of the bulk crystals was confirmed by XRD. The prepared bulk crystal samples were stored in DMF for subsequent characterization.
[0022] The fluorescent MOF prepared in the above embodiments, the fluorescent MOF material prepared in Example 2 was selected for structural characterization: The prepared crystals were tested for X-ray single crystal structure on a Bruker single crystal diffractometer equipped with a cryogenic system and a CCD detector.
[0023] Under the conventional loading method (using crystal glue, silicone oil or AB glue to quickly load the sample), in order to protect the single crystal of the test sample, the MOF crystal was placed in a high-purity boron capillary with a diameter of 0.2 mm, and the crystal was protected with DMF. The capillary containing the crystal was then fixed to the crystal stage and the single crystal structure was tested. MOF uses Mo-Ka radiation (λ= 0.71073 Å) and collects data according to the Laue group strategy. After data restoration, the Patterson method is used to determine the position of the metal atoms, and then the difference Fourier method is used to calculate the coordinates of all non-hydrogen atoms, and the theoretical hydrogenation method is used to obtain the position of the hydrogen atoms, and the least squares method is used to correct the structure. The structural analysis work was completed using the SHELXTL-97 and OLEX-2 program packages.
[0024] Basic crystallographic data of fluorescent MOF: T = 293 K; Crystal system: Hexagonal; spacegroup: R - 3 ; a =20.2178 (3) Å; b =20.2178 (3) Å; C=41.8385 (7) Å; α=90°, β=90°, γ=120°, V = 14810.6 (4) Å 3 ; Z = 36; ρ calcd =1.513 Mg m -3 ; μ =3.84 mm -1 ; θ max =76.8°; 3424independent reflections ( R int =0.019); R 1=0.112; wxya 2 = 0.470; GOF = 2.30. Fluorescent MOF belongs to the Hexagonal crystal system R¯3 space group. Figure 3 The SBU of the fluorescent MOF shown in a) is two Zn 2+ ions, Zn1 and Zn2, have a five-coordinated trigonal bipyramidal geometry, while the tdc ligand adopts a coordination mode: (η 1 -η 1 )-(η 1 -η 2 -μ2)-μ4(tdc)( Figure 3 b)). Two Zn(II) ions are bridged by two DMF dimers and the carboxyl groups of four different tdc ligands to form a binuclear [Zn2(COO)4(O)2]. These binuclear units are connected in the ab plane by four tdc ligands to form a two-dimensional layer with a 4-connected kgm (kagome) network ( Figure 3 a)). A new fluorescent MOF uses the center point of the binuclear unit as a node and the ligand is simplified to a line, forming a 4-connected kgm network layer ( Figure 3 d)). The three-dimensional stacking diagram of a new type of fluorescent MOF is a stacking of two-dimensional layers in the c-axis direction to form a one-dimensional channel ( Figure 3 c). From a topological point of view, the framework of a novel fluorescent MOF can be described as a kgm network with Schlafli notation ( Figure 3d)).
[0025] The original synthetic sample of fluorescent MOF was washed with DMF, filtered, and dried at room temperature before powder diffraction test. The measured powder diffraction pattern of fluorescent MOF is shown in Figure 4 As shown in the figure, the main diffraction peaks (2θ) are located at 6.809°, 9.72°, 12.96°, and 15.50°, corresponding to the (100), (110), (-1-11), and (-111) crystal planes, respectively. The measured Bragg diffraction peak positions and intensities are consistent with the fitting spectrum based on the single crystal structure, proving that the tested sample is a single phase and the product is single under experimental conditions.
[0026] To test the thermal stability of the fluorescent MOF, thermogravimetric (TG) analysis was performed ( Figure 5 , 30-800 o C, oxygen flow rate 10 mL / min, heating rate 10 o C / min). The results show that a new type of fluorescent MOF in N2:O2=4:1 atmosphere has a high o C. As the temperature increases, a significant weight loss (26.9%) occurs, and the weight loss ratio matches the loss of 1.5 DMF guest molecules per molecular unit (the theoretical value is 26.21%). The mass balance can then be maintained at nearly 400 o The C framework rapidly undergoes thermal decomposition accompanied by dramatic weight loss, and the final residue mass ratio is 22.9%, which is close to the theoretical value of ZnO (theoretical value is 19.46%), so the final residue may be ZnO.
[0027] The results of fluorescence MOF testing at room temperature were as follows: Figure 6 As shown in a, a new type of fluorescent MOF in λ ex = The emission spectrum obtained under the excitation wavelength of 396 nm is 469 nm, and the fluorescent MOF is shown to emit blue light through the CIE chromaticity diagram ( Figure 6 b). The fluorescent MOF prepared by the present invention has good application prospects in the fields of luminescent materials, chemical sensors, environment, etc. The above embodiments are merely descriptions of preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a fluorescent MOF, characterized in that: The fluorescent MOF has {[Zn (tdc) (DMF)]·1.5DMF} n The fluorescent MOF is prepared by the following steps: (1) The organic ligands thiophene-2,5-dicarboxylic acid (H2tdc), Zn 2+ The salt is weighed in a molar ratio of (0.15-0.25): (0.15-0.25), added into N,N-dimethylformamide (DMF) solvent, and stirred with a magnetic stirrer in air to obtain a colorless transparent clear liquid; (2) Transfer the obtained colorless transparent clear liquid into a glass bottle with an aluminum cap, place it in an oven and heat it to 90-120°C for 40-72 hours, then cool it to room temperature at a rate of 10°C per hour; (3) Washing with DMF yields a large amount of colorless, transparent block crystals; the prepared crystals are fluorescent MOFs.
2. The method for preparing a fluorescent MOF according to claim 1, characterized in that: The Zn 2+ The salt is selected from at least one of Zn(NO3)2•6H2O, zinc acetate and zinc sulfate.
3. The method for preparing a fluorescent MOF according to claim 1, characterized in that: Among them, H2tdc and Zn 2+ The molar weights of the salts are (0.15-0.25) mmol and (0.15-0.25) mmol respectively, and the solvent is DMF in an amount of 8-12 ml.
4. The method for preparing a fluorescent MOF according to claim 1, characterized in that: The stirring time in step (1) is 5-15 min.
5. The method for preparing a fluorescent MOF according to claim 1, characterized in that: In step (2), the heating temperature is 100° C. and the heating time is 48 h.
6. The method for preparing a fluorescent MOF according to claim 1, characterized in that: Basic crystallographic data of the fluorescent MOF: T = 293 K; Crystal system: Hexagonal; space group: R-3; a = 20.2178(3) Å; b = 20.2178 (3) Å; C = 41.8385 (7) Å; α = 90°, β = 90°, γ = 120°, V = 14810.6 (4) Å3; Z = 36; ρcalcd = 1.513 Mg m-3; μ = 3.84 mm-1; θmax = 76.8°; 3424 independentreflections (Rint = 0.019); R1 = 0.112; wR2 = 0.470; GOF = 2.
30.
7. The method for preparing a fluorescent MOF according to claim 1, characterized in that: The fluorescent MOF belongs to the Hexagonal crystal system R-3 space group; the SBU of the fluorescent MOF is two Zn 2+ The ions, Zn1 and Zn2, are both five-coordinated trigonal bipyramidal geometric structures, while the tdc ligand adopts a coordination mode: (η1-η1)-(η1-η2-μ2)-μ4 (tdc); the two Zn (II) ions are bridged by two DMF dimers and the carboxyl groups of four different tdc ligands to form a binuclear [Zn2(COO)4(O)2]; these binuclear units are connected by four tdc ligands in the ab plane to form a two-dimensional layer with a 4-connected kgm (kagome) network; the fluorescent MOF uses the center point of the binuclear unit as a node, and the ligands are simplified to lines, forming a layer of a 4-connected kgm network; the three-dimensional stacking diagram of the fluorescent MOF is the stacking of two-dimensional layers in the c-axis direction to form a one-dimensional channel; from a topological point of view, the framework of the fluorescent MOF can be described as a kgm network with Schlafli symbols.
8. The method for preparing a fluorescent MOF according to claim 1, characterized in that: The fluorescent MOF was washed with DMF, filtered, and dried at room temperature before powder diffraction testing. The main diffraction peaks (2θ) were located at 6.809°, 9.72°, 12.96°, and 15.50°, corresponding to the (100), (110), (-1-11), and (-111) crystal planes, respectively.
9. The method for preparing a fluorescent MOF according to claim 1, characterized in that: The emission spectrum of the fluorescent MOF tested at an excitation wavelength of λex=396 nm is 469 nm, and the CIE chromaticity diagram shows that it emits blue light.